Evaluation of Health Literacy of Type 2 Diabetic Patients Referred to Diabetes Clinic of Arak City and Related Demographic Factors - Milad Ansari; Pegah Mohaghegh; Bahman Sadeghi-sedeh; Fatemah Rafiei (Mashhad University of Medical Sciences, 2020)
Background and Objective: Type 2 diabetes is a non-communicable disease with silent epidemics and a growing health problem. Due to the role of health literacy in control of diabetes, in this study, the level of health literacy and its relationship with demographic factors will be examined in Emam Reza Clinic of arak.Materials and Methods: In this descriptive-analytical cross-sectional study, 201 diabetic patients who had referred to the diabetes clinic of Imam Reza Clinic in Arak in 1398 were entered in the study by available sampling method. The Health Literacy Questionnaire (HELIA) was completed by the physician in an interview with patients. data was entered into statistical software spss23 and analyzed with statistical tests (Mann- Whitney Test, and Kruskal-Wallis).Results: The Means age of patients was 57.37 ± 12.93 years. Most patients (62.7%) were women. The average total health literacy was 55.20 ± 22.14. The highest literacy level was in the accessibility dimension )60.03 ± 32.73(and the lowest in the reading dimension (46.45 ± 21.73(. Health literacy was lower in the elderly and higher in men and people living in the city (p = 0.0001). Health literacy also increases with education and it is higher in Employees and students (p = 0.0001).Conclusion: According to the results of study, the level of health literacy in diabetic patients is low and it is related with age, gender, education, occupation and place of residence of diabetic patients. promoting health literacy of patients, it is necessary to help control of diabetes and prevent its chronic complications.